The Influence of Profitability, Liquidity, Solvency and Company Size on Audit Report Lag in Infrastructure Sector Companies Listed on the IDX in 2019-2022 - Bong, David Christian; Sondakh, Jullie J; Korompis, Claudia W.M (Formosa Journal of Multidisciplinary Research, 2024)
The amount of time the auditor took to complete the audit report, as measured from the book's closing date to the audit report's release date, is known as the audit report lag. The goal of this research was to assess the impact of profitability, liquidity, solvency, and firm size on audit report lag in infrastructure companies listed on the Indonesia Stock Exchange between 2019 and 2022. This is a type of quantitative study that employs a sample selection methodology known as purposive sampling. There are 32 company samples selected from 69 companies. Multiple linear regression was used to examine the data in this study. IBM SPSS 25 is the statistical processing application that was used. The findings of this study's analysis show that both profitability and solvency have a major impact on audit report latency. While liquidity and business size have no substantial impact on the audit report latency of Indonesian Stock Exchange-listed infrastructure companies.